Consequences of objective self-awareness during exercise. Issue 2 (31st July 2015) - Cornick, Jessica E; Blascovich, Jim
Although exercise is recommended by healthcare professionals for nearly everyone, adverse reactions can occur following exercising for some overweight individuals. The reported study investigated the cardiovascular consequences of exercise in a stressful environment. In all, 60 females completed two baseline and one biking (i.e. ergometer) periods while cardiovascular and self-report measures were recorded. Findings indicated that those who are more self-aware showed cardiovascular response patterns indicative of threat. Additionally, post-task exercise self-efficacy levels predicted intentions to exercise at a demanding level in the coming week. These findings suggest exercise may exacerbate health issues for some individuals for whom it is recommended.